The financial inclusion agenda: Examining the role of conventional banks in deepening access to formal credit - Abdul Malik Iddrisu; Michael Danquah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Using a unique district-level panel data set, we investigate the effect of banking system penetration on financial inclusion in Ghana. To purge potential endogeneity bias in the underlying relationship, we exploit a change in the policy environment of the Ghanaian banking system to instrument for banking system penetration. We show, first, that the switch from a compartmentalized system of banking to a universal banking system in Ghana has resulted in an expansion of banks' branch networks, which has benefited hitherto financially less developed districts. Second, our instrumental variable evidence suggests that banking system penetration promotes financial inclusion-notably, access to bank credit and to formal credit. The results of this paper provide important insights into the role of policy in enhancing financial inclusion.
Keywords: C23; G28; G21; O16; 330; financial sector development; banking system penetration; financial inclusion; pseudo panel; Ghana